Analysis of the Determinants of Sustainability Report Disclosure and the Moderating Role of Audit Quality - Puspasari, Dian; Djaddang, Syahril (Riviera Publishing, 2025)
This study aims to analyze the determinants of sustainability report disclosure and examine the moderating role of audit quality in this relationship. The independent variables investigated include firm size, profitability, leverage, and institutional ownership. This research employs a quantitative approach using secondary data derived from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange. The data were analyzed using Moderated Regression Analysis (MRA) to test both direct effects and interaction effects. The findings reveal that firm size and institutional ownership have a significant positive effect on sustainability report disclosure, while profitability and leverage show no significant influence. Furthermore, audit quality is found to moderate the relationship between firm size and institutional ownership with sustainability report, but not for profitability and leverage disclosure. These results highlight the importance of audit quality in enhancing corporate transparency and accountability, particularly in sustainability reporting which has increasingly attracted stakeholder attention.